Low-frequency green functions asymptotics in uniaxial and biaxial nematic liquid crystals - Matskevych, V.T. (Вопросы атомной науки и техники, 2012)
Uniaxial and biaxial nematic liquid crystals are examples of the complicated condensed matters possessing an internal microstructure shown on macroscopic level in the form of a number of the physical phenomena and processes. In this work the dynamic behavior of the studied condensed matters in alternative external field is investigated. On the basis of the nonlinear dynamic equations with sources for uniaxial and biaxial nematics the general analytical expressions of low-frequency Green functions asymptotics are obtained and the analysis of their features in the region of small wave vectors and frequencies is carried out.